Canadian Cardiovascular Society 2009 Consensus Conference on the management of adults with congenital heart disease: Complex congenital cardiac lesions - Silversides, Candice K (Pulsus Group Inc, 2010)
With advances in pediatric cardiology and cardiac surgery, the population of adults with congenital heart disease (CHD) has increased. In the current era, there are more adults with CHD than children. This population has many unique issues and needs. They have distinctive forms of heart failure and their cardiac disease can be associated with pulmonary hypertension, thromboemboli, complex arrhythmias and sudden death. Medical aspects that need to be considered relate to the long-term and multisystemic effects of single ventricle physiology, cyanosis, systemic right ventricles, complex intracardiac baffles and failing subpulmonary right ventricles. Since the 2001 Canadian Cardiovascular Society Consensus Conference report on the management of adults with CHD, there have been significant advances in the field of adult CHD. Therefore, new clinical guidelines have been written by Canadian adult CHD physicians in collaboration with an international panel of experts in the field. Part III of the guidelines includes recommendations for the care of patients with complete transposition of the great arteries, congenitally corrected transposition of the great arteries, Fontan operations and single ventricles, Eisenmenger’s syndrome, and cyanotic heart disease. Topics addressed include genetics, clinical outcomes, recommended diagnostic workup, surgical and interventional options, treatment of arrhythmias, assessment of pregnancy risk and follow-up requirements. The complete document consists of four manuscripts, which are published online in the present issue of The Canadian Journal of Cardiology. The complete document and references can also be found at www.ccs.ca or www.cachnet.org.